DYNAMICS OF SYMBOLS AS TRANSCULTURAL POETICS - Adilson Vagner de Oliveira (Abril, 2015)
This paper aims at reflecting on the poetic possibilities of productions that take the encounter of cultures as compositional element to discuss issues beyond the limits of literature and culture. Thus, we sought to demonstrate the dynamics of cross-cultural symbolic systems through the political play A Revolta da Casa dos Ídolos (1978) by Pepetela in order to propose new understandings of the social reality in contemporary Angola.